There are
2 apples (A) and
5 bananas (B) initially, and then let
x apples, and
y bananas be added to get to new ratio of
apples (A) to
bananas (B) of
1:
2.
Statement (1):
\(x = \frac{2}{3} y\)
Sufficient, have the relation between
x and
y, so can plug into the ratio equation to solve for
x and then
y.
To illustrate this:
Apples :
Bananas\(\frac{(2 + x)}{(5 + y)} = \frac{1}{2}\)
\((2 + \frac{2y}{3})/(5 + y) = \frac{1}{2}\)
\(2(2+ \frac{2}{3} y) = 5 + y\)
\(4 + \frac{4}{3} y = 5 + y\)
\(y = 3\)\(x = 2/3 y\)
\(x = 2\)Statement (2):
\(x + y = 5\)
Also sufficient since have the total of
x and
y.
Still can solve for
x to illustrate:
\(y = 5 - x\)
\(\frac{(2 + x)}{(5 + 5 - x)} = \frac{1}{2}\)
\(\frac{(2 + x)}{(10 - x)} = \frac{1}{2}\)
\(2(2 + x) = 10 - x\)
\(x = 2\)Jcpenny
There were 2 apples and 5 bananas in a basket. After additional apples and bananas were placed in the basket, the ratio of the number of apples to the number of bananas was 1/2. How many apples were added?
(1) The number of apples added was 2/3 the number of bananas added.
(2) A total of 5 apples and bananas were added.